Relaxin ameliorates high glucose-induced cardiomyocyte hypertrophy and apoptosis via the Notch1 pathway - Wei, Xiao (Exp Ther Med, 2018)
The present study aimed to investigate the role of relaxin (RLX) on high glucose (HG)-induced cardiomyocyte hypertrophy and apoptosis, as well as the possible molecular mechanism. H9c2 cells were exposed to 33 mmol/l HG with or without RLX (100 nmol/ml). Cell viability, apoptosis, oxidative stress, cell hypertrophy and the levels of Notch1, hairy and enhancer of split 1 (hes1), atrial natriuretic polypeptide (ANP), brain natriuretic peptide (BNP), manganese superoxide dismutase (MnSOD), cytochrome C and caspase-3 were assessed in cardiomyocytes. Compared with the HG group, the viability of H9c2 cells was increased by RLX in a time- and dose-dependent manner, and was accompanied with a significant reduction in apoptosis. Furthermore, RLX significantly suppressed the formation of reactive oxygen species and malondialdehyde, and enhanced the activity of SOD. In addition, the levels of ANP, BNP, cytochrome C and caspase-3 were increased and Notch1, hes1 and MnSOD were inhibited in the HG group compared with those in the normal group. However, the Notch inhibitor DAPT almost abolished the protective effects of RLX. These results suggested that RLX protected cardiomyocytes from HG-induced hypertrophy and apoptosis partly through a Notch1-dependent pathway, which may be associated with reducing oxidative stress.